2020
DOI: 10.3390/life10110264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Ion Particle Irradiation on Spore Germination of Bacillus spp. from Extremely Hot and Cold Environments

Abstract: Extremophiles are optimal models in experimentally addressing questions about the effects of cosmic radiation on biological systems. The resistance to high charge energy (HZE) particles, and helium (He) ions and iron (Fe) ions (LET at 2.2 and 200 keV/µm, respectively, until 1000 Gy), of spores from two thermophiles, Bacillushorneckiae SBP3 and Bacilluslicheniformis T14, and two psychrotolerants, Bacillus sp. A34 and A43, was investigated. Spores survived He irradiation better, whereas they were more sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 91 publications
2
11
0
Order By: Relevance
“…A phenomenon that has been observed in OD measurements of Bacillus sp. when they undergo the stressors of nutrient limitation [56][57][58][59][60]. For the strains that exhibited reduced growth in the higher fluid concentrations (Bacillus MKS3, Staphylococcus MKS13, Halomonas MKS19, Bacillus MKS28), this is possibly due to the changes in concentrations of salts or toxicity from some of the elements in the Rocknest fluid chemistry (e.g., Mn, Al, Fe; [61]) reaching concentrations that are inhibitory for the affected stains.…”
Section: Variation In Viability Of the Anderton Brine Springs Isolatesmentioning
confidence: 99%
“…A phenomenon that has been observed in OD measurements of Bacillus sp. when they undergo the stressors of nutrient limitation [56][57][58][59][60]. For the strains that exhibited reduced growth in the higher fluid concentrations (Bacillus MKS3, Staphylococcus MKS13, Halomonas MKS19, Bacillus MKS28), this is possibly due to the changes in concentrations of salts or toxicity from some of the elements in the Rocknest fluid chemistry (e.g., Mn, Al, Fe; [61]) reaching concentrations that are inhibitory for the affected stains.…”
Section: Variation In Viability Of the Anderton Brine Springs Isolatesmentioning
confidence: 99%
“…The GCRs are composed of high-energy protons, α-particles, and high atomic number nuclei and energy (HZE) ions that in turn represent about 1% of GCRs and are the major cause of the lethal effects of this radiation. The biological effects produced by an HZE have been extensively studied in a variety of space experiments or on ground simulation facilities using the biological dosimeter spores of Bacillus subtilis species [2][3][4][5]. These studies showed that the ionizing radiation effects depend upon both the delivered dose and the type of radiation; indeed, the LET value directly correlates with the number of changed cell structures and molecules that are passed through the particle's path [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects produced by an HZE have been extensively studied in a variety of space experiments or on ground simulation facilities using the biological dosimeter spores of Bacillus subtilis species [2][3][4][5]. These studies showed that the ionizing radiation effects depend upon both the delivered dose and the type of radiation; indeed, the LET value directly correlates with the number of changed cell structures and molecules that are passed through the particle's path [2][3][4][5]. Fe, Ar, and He ions are high-LET particles (>2 keV/mm), and they can be harmful by means of two different processes, i.e., "direct hits" and "indirect hits": in the first case, the cell is in the track core of the HZE particle, and it is passed via the particle; in the second case, the cell is hit only by high-energy secondary electrons, i.e., δ-rays, which are produced by interaction of the HZE with the biological target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modern-day mat ecosystems resemble life during the Precambrian era, when the biosphere was mostly microbial and benthic [ 5 , 6 , 7 , 8 ]. Fortunately, even today, microbial mats similar to life in the shallow, anoxic, sometimes euxinic (high hydrogen sulfide, low dissolved oxygen) seas of the early biosphere thrive in several globally distributed refugia under extreme conditions of moisture, salinity, pH, temperature, and oxygen [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Indeed, a great variety of living microbial mats with a diversity of structural and functional characteristics are found in extant extreme ecosystems all over the world ranging from subglacial lakes to deep sea thermal vents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%